Parthenolide induces rapid thiol oxidation that leads to ferroptosis in hepatocellular carcinoma cells - LoBianco, Francesca V.; Krager, Kimberly J.; Johnson, Erica; Godwin, Christopher O.; Allen, Antino R.; Crooks, Peter A.; Compadre, Cesar M.; Borrelli, Michael J.; Aykin-Burns, Nukhet (Frontiers in Toxicology, 2022)
Hepatocellular carcinoma (HCC) is both a devastating and common disease. Every year in the United States, about 24,500 men and 10,000 women are diagnosed with HCC, and more than half of those diagnosed patients die from this disease. Thus far, conventional therapeutics have not been successful for patients with HCC due to various underlying comorbidities. Poor survival rate and high incidence of recurrence after therapy indicate that the differences between the redox environments of normal surrounding liver and HCC are valuable targets to improve treatment efficacy. Parthenolide (PTL) is a naturally found therapeutic with anti-cancer and anti-inflammatory properties. PTL can alter HCC’s antioxidant environment through thiol modifications leaving tumor cells sensitive to elevated reactive oxygen species (ROS). Investigating the link between altered thiol mechanism and increased sensitivity to iron-mediated lipid peroxidation will allow for improved treatment of HCC. HepG2 (human) and McARH7777 (rat) HCC cells treated with PTL with increasing concentrations decrease cell viability and clonogenic efficiency in vitro. PTL increases glutathione (GSH) oxidation rescued by the addition of a GSH precursor, N-acetylcysteine (NAC). In addition, this elevation in thiol oxidation results in an overall increase in mitochondrial dysfunction. To elucidate if cell death is through lipid peroxidation, using a lipid peroxidation sensor indicated PTL increases lipid oxidation levels after 6 hours. Additionally, western blotting reveals glutathione peroxidase 4 (GPx4) protein levels decrease after treatment with PTL suggesting cells are incapable of preventing lipid peroxidation after exposure to PTL. An elevation in lipid peroxidation will lead to a form of cell death known as ferroptosis. To further establish ferroptosis as a critical mechanism of death for HCC in vitro, the addition of ferrostatin-1 combined with PTL demonstrates a partial recovery in a colony survival assay. This study reveals that PTL can induce tumor cell death through elevations in intracellular oxidation, leaving cells sensitive to ferroptosis.